Induced Voltages on a Gas Pipeline due to Lightning Strikes on Nearby Overhead Transmission Line - Ali I Elgayar; Zulkurnain Abdul-Malek (Institute of Advanced Engineering and Science, 2016)
The purpose of this paper is to investigate the severity of lightning induced voltages on a gas pipeline installed in parallel with overhead transmission line using two different simulation packages. The results from this study using CDEGS, which solves a given problem based on electromagnetic computations, reveal that the induced voltages on the pipeline are more accurate compared to that obtained by PSCAD simulation, which is based on the circuit approach. Unlike PSCAD, CDEGS considers many salient factors such as soil model, inductive, capacitive and conductive couplings, and multiple soil structures. Models of a double circuit 132kV transmission line, gas pipelines, soil with different resistivities and variable lightning surges were developed. The effects of pipelines located at various heights above ground and distance of pipeline from the power lines were also studied. Compared to previously published work using PSCAD, it is found that CDEGS has given more accurate results. Several findings which were not possible using PSCAD were observed such as the effect of soil structure on induced voltage and multiple layers soil. This also led to better understanding of the conductive coupling from lightning strikes and fault conditions. The modeling work using CDEGS not only useful for providing more reliable data for further protection and mitigation techniques, but is also very versatile to study the effects of various other important factors affecting the induced voltage on the pipelines.